PENINGKATAN HASIL BELAJAR DRIBBLE SEPAK BOLA MELALUI PENDEKATAN MODIFIKASI PERMAINAN SEPAKBOLA - PUJIADI, (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Football as a sport that is part of the physical education, football is a product and process are inseparable. This suggests that in the process of teaching and learning football for obtain good results, students should be involved as a direct object given physical education through physical activity. Interaction with students that went well will encourage the development of students into a better direction again. Football is not just a practice, but also a theory of learning that students should be actively involved in interacting directly observe and practice and apply the concepts learned. The purpose of this study is to determine how much is there and increased influence of learning with modified forms football games approach on learning outcomes in SDN Sambikerep soccer dribble I/479 Surabaya. The samples were fifth grade students of SDN Sambikerep I/479 Surabaya is 30 students by using cluster random sampling technique. Method in this study using quantitative descriptive design one group pretest-posttest design. And the process of data collection was done by using a dribbling test adopted from Nurhasan (2003). It can be concluded that: 1) There is an effect 2) Effect of increased learning approach modification form football games on learning outcomes in SDN Sambikerep soccer dribble I/479 Surabaya at 0.82%. Keywords : Soccer Game Modification